Devices & desires gender, technology, and American nursing - Sandelowski, Margarete (Studies in social medicine, 2000)
The author traces the relationship between nursing and technology from the 1870s to the present. She argues that while technology has helped shape and intensify persistent dilemmas in nursing, it has also both advanced and impeded the development of the nursing profession.